EFFECT OF BROCCOLI (Brassica oleracea L.var. italica) FLOUR ADDITION ON CARP FISH (Laptobarbus hoevenii) NUGGET TO CONSUMER ACCEPTANCE - Mitra, Siswanda; ', Desmelati; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on March 2017 in Fishery Products Technology and Fishery Products Chemical Laboratorium Faculty of Fisheries and Marine Sceince Universitas Riau Pekanbaru. The purpose of this study was to determine the effect of broccoli (Brassica oleracea L.var. italica) flour addition on carp fish (Laptobarbus hoevenii) nugget to consumer acceptance. The experimental methode was used in this research which was processing of carp fish nugget with using broccoli flour as a binder. The Completely Randomized Design (CRD) was used as experimental design with 5 treatment levels i.e B0 (0% of broccoli flour), B1 (15% of broccoli flour), B2 (25% of broccoli flour), B3 (50% of broccoli flour), and B4 (75% of broccoli flour). The experiment was repeated for 3 times so that the number of experimental units in this study was 15 units. Based on organoleptic analysis that N2 (25% of broccoli flour) was most preferred by the consumer acceptance, with (appearance 7.542, textures 7.542, odor 7.446 and taste 7.425), moisture content 61.58%, protein content 14.65% , fat content 5.33%, and fiber content 3.03%.Keywords: Broccoli Flour, Nugget, Laptobarbus hoevenii